Computing-network intelligence: research progress and prospects - ZHU Hailong; YANG Fan; JIANG Ruyi; JIA Qingmin; ZHOU Xiaomao; XIE Renchao; HUANG Tao (Tongxin xuebao)
Although the computing power network (CPN) can connect via the Internet and flexibly schedule computing resources, it still lacks intelligence and flexibility in practical applications. To address the need for enhanced intelligence in computing power networks, the background and concept of the computing-network intelligence (CNI) were first introduced briefly. Then, followed by the proposal of a novel basic architecture and operational mechanism for CNI, intelligent resource allocation and service scheduling of multi-dimensional resources were achieved through key technologies such as computing-network perception, intelligent decision-making, computing power routing, automation, and self-optimization. Finally, future research directions and technical challenges were discussed. CNI is recognized as an inevitable trend for the future, effectively addressing issues such as complex operational processes, excessive reliance on human experience, and difficulties in adapting to dynamically changing environments.